2011
DOI: 10.1093/infdis/jir341
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Genital Human Papillomavirus Among Females in the United States, the National Health and Nutrition Examination Survey, 2003–2006

Abstract: HPV infection is common among US females, with the highest burden of infection found in young females 20-24 years of age. Monitoring trends in HPV type distribution will contribute to our understanding of the early impact of HPV vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
268
6
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(317 citation statements)
references
References 31 publications
32
268
6
3
Order By: Relevance
“…In women, the prevalence of HPV was found to be lowest among 14-19-year-old females (32.9%) and highest among 20-24-year-old females (53.8 %) (Hariri et al, 2011).…”
Section: Hpv Vaccine Knowledge and Perceived Risk Of Cervical Cancermentioning
confidence: 89%
“…In women, the prevalence of HPV was found to be lowest among 14-19-year-old females (32.9%) and highest among 20-24-year-old females (53.8 %) (Hariri et al, 2011).…”
Section: Hpv Vaccine Knowledge and Perceived Risk Of Cervical Cancermentioning
confidence: 89%
“…Extractions and testing on vaginal swab specimens were performed at the Centers for Disease Control and Prevention (CDC), with details described elsewhere. 14,28 Briefly, vaginal swabs were analyzed for HPV DNA by L1 consensus polymerase chain reaction followed by type-specific hybridization. All specimens were hybridized to the typing strip that included probes for 37 HPV types, including high-risk types (16, 18, 31,33, 35, 52, 58, 39 …”
Section: Methodsmentioning
confidence: 99%
“…The result showed a difference of opinion while comparing to studies done by others (Cite Table2).The overall prevalence of HPV was 42.5%in the US (Susan Hariri et al,. 2011) [16] , 13.3% in southeast China (Ye et al 2010) [17] , 15.1% in the UK (Cotton et al 2007) [18] , and 22.7% in Greek population (PetroulaStamatakiet al,2010) [19] . The evaluation of our study showed a lower HPV prevalence in cervical smears compared with the study done by Laikangbam P et al, (2007) [20] in Sikkim and Kulkarni SS et al, (2011) [21] in Karnataka and in Andhra Pradesh (Pavaniet al,.2005) [24] but similar results were found by study done in Uttar Pradesh (Srivastava S et al,2012) [22] and in Eastern India (Dutta S et al,.…”
Section: ) the Statistical Analysismentioning
confidence: 99%